Association of estimated liver fibrosis with carotid but not femoral atherosclerotic burden: the ILERVAS cohort - León-Mengíbar, Josep; Malagón, María M.; Bermúdez-López, Marcelino; Valdivielso, José Manuel; Pamplona, Reinald; Torres, Gerard; Mauricio, Dídac; Castro, Eva; Fernández, Elvira; Caixàs, Assumpta; Hernández, Marta; Lopez-Cano, Carolina; et al. (Frontiers in Endocrinology, 2026)
IntroductionAdvanced liver fibrosis, a key complication of metabolic dysfunction-associated steatotic liver disease, has been increasingly linked to extrahepatic conditions, including type 2 diabetes, obesity, and cardiovascular disease. However, the specific association of liver fibrosis in the development and progression of subclinical atheromatous disease across vascular territories remains poorly understood. This study evaluates the utility of two non-invasive indices to predict liver fibrosis and their associations with subclinical atheromatous plaque burden and distribution.MethodsAtheromatous plaque burden (plaque presence, number, and total area) was assessed in the carotid and femoral territories via ultrasonography in 3,981 middle-aged participants without known cardiovascular disease, diabetes, or liver disease from the ILERVAS cohort (ClinicalTrials.gov Identifier: NCT03228459). The fibrosis-4 (FIB-4) and the NAFLD Fibrosis Score (NFS) were evaluated. FIB-4 risk categories were defined as low (<1.30), intermediate (1.30–2.67), and high (>2.67).ResultsParticipants in the intermediate and high-risk FIB-4 categories exhibited a higher prevalence of carotid atheromatous disease (56.8% vs. 49.5%, p<0.001), a greater number of plaques (p<0.001), and a larger total plaque area (p=0.007). Multivariable analyses confirmed FIB-4 as an independent predictor of carotid plaque burden (OR: 1.14, 95% CI 1.05-1.24, p=0.003), even adjusting for traditional cardiovascular risk factors. Moving from low to high FIB-4 cut-offs was associated with 12.6% higher odds of carotid atherosclerosis. NFS was also independently associated with carotid atheromatosis (OR 1.10, 95% CI 1.05–1.15, p<0.001). No significant associations were found in the femoral territory for either index.ConclusionsEstimated liver fibrosis, particularly FIB-4, is a valuable marker for identifying carotid subclinical atherosclerosis in populations without known liver disease. These findings highlight the importance of vascular territory-specific evaluations and support their utility in integrated liver and cardiovascular risk assessment strategies.